Sensory Processing and Maladaptive Behavior: Profiles Within the Down Syndrome Phenotype. (3rd September 2019) - Will, Elizabeth A.; Daunhauer, Lisa A.; Fidler, Deborah J.; Raitano Lee, Nancy; Rosenberg, Cordelia Robinson; Hepburn, Susan L.
Abstract: Aim : Sensory processing impairments are well characterized in children with neurodevelopmental disorders, particularly autism, and have been associated with maladaptive behaviors. However, little is known regarding sensory processing difficulties within Down syndrome, or how these difficulties may influence maladaptive behavior. This study aims to characterize sensory processing difficulties within the Down syndrome phenotype and determine the influence of processing difficulties on maladaptive behavior. Methods : To explore this issue, we administered the Short Sensory Profile and the Developmental Behavior Checklist to parents or primary caregivers of young children with DS ( N  = 49; M nonverbal mental age (NVMA) = 30.92 months (SD = 12.30); M chronological age (CA) = 67.04 (SD = 25.13). Results : Results indicated that Low Energy/Weak, Under-responsive/Seeks Sensation, and Auditory Filtering were the areas of greatest sensory regulation difficulty, and that Self-Absorbed behavior and Disruptive/Antisocial behavior were elevated areas of maladaptive behavior. Multivariate regression analyses indicated that Under-responsive/Seeks Sensation was the only sensory regulation domain significantly associated with Self-Absorbed and Disruptive/Antisocial behavior. Conclusion : Findings indicate a consistent pattern of sensory processing impairments and associations with maladaptive behavior in children with DS. Implications for interventions are discussed.